Redox-Mechanisms of Molecular Hydrogen Promote Healthful Longevity - Md. Habibur Rahman; Eun-Sook Jeong; Hae Sun You; Cheol-Su Kim; Kyu-Jae Lee (MDPI AG, 2023)
Age-related diseases represent the largest threat to public health. Aging is a degenerative, systemic, multifactorial and progressive process, coupled with progressive loss of function and eventually leading to high mortality rates. Excessive levels of both pro- and anti-oxidant species qualify as oxidative stress (OS) and result in damage to molecules and cells. OS plays a crucial role in the development of age-related diseases. In fact, damage due to oxidation depends strongly on the inherited or acquired defects of the redox-mediated enzymes. Molecular hydrogen (H2) has recently been reported to function as an anti-oxidant and anti-inflammatory agent for the treatment of several oxidative stress and aging-related diseases, including Alzheimer's, Parkinson's, cancer and osteoporosis. Additionally, H2 promotes healthy aging, increases the number of good germs in the intestine that produce more intestinal hydrogen and reduces oxidative stress through its anti-oxidant and anti-inflammatory activities. This review focuses on the therapeutic role of H2 in the treatment of neurological diseases. This review manuscript would be useful in knowing the role of H2 in the redox mechanisms for promoting healthful longevity.